Juridical Analysis of Supreme Court Decisions on Gender Bias in Domestic Violence Case Rulings - Jannah, Nadifa; Adab, Jauhirul (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Domestic Violence (DV) is a subject matter that disturbs human rights, but is usually neglected or inadequately dealt with in the judicial system, also at the Supreme Court level. This study is intended to make a juridical analysis of the gender bias in the decision of the Supreme Court on domestic violence cases in Indonesia. The research would apply a qualitative-juridical approach with a case-study design and analyze 10 purposively selected Supreme Court rulings from 2015 to 2024, using a gender-bias indicator framework to examine them. The study shows that 70% have exhibited gender bias in the ruling, counted by stereotypes about women, ignoring power relations, and also through legal reasoning that does not consider substantive justice. Only three decisions show clear and constant consideration for the victims, aligning with gender equality principles and international obligations such as the CEDAW. This study aims to develop an interdisciplinary approach between law and gender studies through a replicable, evaluative framework for assessing gender bias. The findings subsequently bear practical implications for the preparation of technical guidelines and judicial training and reform for a fairer and much more equitable justice system for victims of domestic violence. Ultimately, these insights underline the urgent need for judicial reform in Indonesia, particularly within the Supreme Court, to strengthen institutional capacity, enhance judges’ gender-sensitive training, and ensure that court decisions truly reflect substantive justice.